191 Dream features of the Italian population across the first and second wave of the COVID-19 pandemic. (3rd May 2021) - Rescott, Marisssa; Conte, Francesca; De Rosa, Oreste; Cellini, Nicola; Malloggi, Serena; Giganti, Fiorenza; Ficca, Gianluca
Abstract: Introduction: The Italian government has responded to the second wave of the COVID-19 pandemic (autumn 2020) with a partial lockdown (PL). Here we aim to investigate the effects of the PL on dream features in the Italian population and to follow up on previous data collected during the total lockdown (TL) effected during the first wave of the pandemic (spring 2020). Methods: Using a longitudinal approach, 214 participants (Mage=36.78±14.2y; 159F) who had participated in a previous survey (April 2020 – TL) completed the same online survey from November 10th to December 1st (PL). The questionnaires administered included the Pittsburgh Sleep Quality Index (PSQI) and a set of specific ad hoc questions on dream features (frequency, length, vividness, emotional tone, relation of content to the current health emergency) and their possible changes relative to the month preceding the lockdown, resulting in four time points (pre-TL, TL, pre-PL, PL). Results: Frequency and length of dreams significantly increased from pre-PL to PL (both p's<.01), while no difference emerged for vividness. As in TL, almost 30% of the subjects reported having COVID-19-related dreams during PL and, among these, 51% reported to face, in these dreams, problematic situations similar to those of their daily life. Both PSQI and dream negative emotionality scores significantly increased from pre-TL to TL, decreased in pre-PL and increased again in PL, indicating a parallel worsening of sleep quality and dream emotionality with both lockdowns. Dream negative emotionality in PL also showed positive correlations with PSQI scores and with negative mood, stress levels, general fear and fear about the COVID-19. Conclusion: In line with the continuity hypothesis on the relationships between dreaming and the wake state, our data confirm that dream features are significantly and immediately affected by major life changes such as those brought about by the COVID-19 pandemic and related restrictions. Interestingly, dream emotionality and subjective sleep quality show a parallel profile across the different time points, suggesting the possible role of sleep quality as a modulating factor on dream affect. Support (if any): N/A